Wybrane obowiązki strażników dostępu w świetle Aktu o rynkach cyfrowych z perspektywy ochrony danych osobowych - Wyderka, Krzysztof (Wydawnictwo C.H. Beck, 2023)
In recent years, digital services and in particular online platforms have played an increasingly important role in the European and global economy. Opportunities created by platform services, combined with potential ill practices of enterprises providing these services, can adversely affect competition and the fundamental rights of end users. There is also a perceivable problem of control of important ecosystems in the digital economy by few large platforms, which are referred to as gatekeepers. In response to these challenges, European Union bodies are setting up a new legal framework to create a more secure digital space and a fair play field to foster innovation, economic growth and competitiveness. Bearing in mind the fact that data, and in particular personal data, is a key asset for the digital economy, new legislation also establishes obligations related to the processing of personal data. Among the recently adopted regulations, the Digital Markets Act (DMA) plays an important role. The purpose of this article is to identify the key obligations of gatekeepers relating to the processing of personal data arising from the provisions of DMA, to identify the interplay between the provisions of the Digital Markets Act and the provisions of the GDPR and the challenges arising from it, and to attempt to clarify doubts.
Keywords: dane osobowe; Akt o rynkach cyfrowych; strażnicy dostępu; podstawowa usługa platformowa; przenoszenie danych; profilowanie